A new species of Microglanis (Siluriformes, Pseudopimelodidae) from lower Rio Tocantins basin, Pará, Brazil, with description of superficial neuromasts and pores of lateral line system - Ruiz, William Benedito Gotto; Shibatta, Oscar Akio (Zootaxa, 2010)
Microglanis robustus, new species, is the first Microglanis to be described from the Rio Tocantins basin, Pará, Brazil, and differs from the congeners by the presence of a cordiform blotch in the nape, instead of a transverse light stripe; neuromasts of the superficial lines surrounded by melanophores; robust body with short snout, head and predorsal distance; and deep caudal peduncle. The mapping of superficial neuromasts and cephalic sensory canals evidenced intra and interespecific polymorphisms and, therefore, of little value for phylogenetic analysis within the genus.